Micro-expansion composite fiber anti-cracking concrete with low hydration heat as well as preparation method and application of micro-expansion composite fiber anti-cracking concrete

By using micro-expanded composite fiber anti-crack concrete with low hydration heat in tunnels and underground engineering, the problem of cracking is easily encountered in concrete lining, which significantly improves cracking performance, compressive and tensile strength, and reduces cracking risk and hydration heat.

CN119912220APending Publication Date: 2025-05-02CHINA RAILWAY DEV INVESTMENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510177625.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In tunnels and underground projects, concrete lining is prone to temperature cracks and shrinkage cracks, resulting in reduced structural bearing capacity and threats to project quality and safety.

Method used

The micro-expanded composite fiber anti-crack concrete with low hydration heat is used to improve the internal structure of the concrete by adding composite fibers, fly ash, expansion agent and water reducing agent, reducing hydration heat and volume shrinkage, and improve compressive, tensile strength and cracking resistance.

Benefits of technology

It significantly improves the crack resistance of concrete, reduces the crack risk of tunnel and underground engineering lining concrete in complex environments, reduces the heat of cement hydration reaction, and improves the volume stability of the material and the value of engineering application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912220A_ABST
    Figure CN119912220A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of tunnel and underground engineering lining concrete, in particular to low-hydration-heat micro-expansion composite fiber anti-cracking concrete as well as a preparation method and application of the low-hydration-heat micro-expansion composite fiber anti-cracking concrete. The concrete is prepared from the following components in parts by weight: 275 to 316 parts of cement, 89 to 130 parts of fly ash, 40 to 125 parts of composite fiber, 0.1 to 0.5 part of air entraining agent, 20 to 25 parts of expanding agent, 2 to 5 parts of water reducing agent, 750 to 850 parts of sand, 402 to 1005 parts of gravel and 150 to 200 parts of water. According to the low-hydration-heat micro-expansion composite fiber anti-cracking concrete and the preparation method and application thereof, on the premise that it is guaranteed that all the components are fully and evenly mixed, the concrete preparation and site construction efficiency can be remarkably improved, the prepared anti-cracking concrete has good compactness, mechanical properties and anti-cracking capacity, and the anti-cracking performance of the concrete is improved. The occurrence risk of temperature cracks and shrinkage cracks is effectively reduced, the preparation steps are simple, field operation is convenient and fast, the construction cost is controllable, and good engineering application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tunnel and underground engineering lining concrete, and in particular to a micro-expansion composite fiber anti-cracking concrete with low hydration heat, and a preparation method and application thereof. Background Art

[0002] In the construction of tunnels and underground projects, affected by factors such as complex construction environment, existing technology level and quality control measures, different types of cracks often appear in concrete linings. For example, a large amount of hydration heat is released during the setting process of concrete, resulting in significant differences in the temperature field and deformation field inside the lining structure, thus causing temperature cracks; the temperature and humidity environment of the tunnel is complex, and the surface moisture of the concrete is lost quickly, resulting in shrinkage cracks on the lining surface. The generation of cracks in the lining concrete not only greatly reduces the structural bearing capacity, but also induces diseases such as seepage and gushing, posing a serious threat to the quality of the project and long-term operational safety.

[0003] Research on anti-cracking technology for lining concrete has always been an important topic of concern in the field of tunnels and underground engineering. Traditional concrete materials have problems such as high hydration heat, significant volume shrinkage, and low tensile strength, which are one of the main causes of cracks. At present, engineering projects usually adopt measures such as adjusting concrete grading, optimizing maintenance measures and construction procedures to control cracking, but for large-volume concrete in complex construction environments, the anti-cracking effect has not yet met expectations.

[0004] At the same time, a variety of anti-cracking concrete materials have been developed at home and abroad. For example, patent CN116332589A provides an environmentally friendly, low-temperature resistant anti-cracking concrete and its preparation method, which improves the long-term anti-cracking performance by adding glass fiber to the concrete; patent CN116375415A discloses a method for preparing polypropylene fiber concrete, which has a significant effect on improving the anti-cracking performance of bridges; patent CN115368084B has developed a high-strength anti-cracking concrete and its preparation method, adding ABS plastic particles to the concrete, and reducing the local stress of the concrete through micro-deformation of the particles, thereby reducing the risk of cracking.

[0005] The research, development and application of the above-mentioned anti-cracking concrete materials are of great significance for controlling the occurrence of cracks and improving the safety of engineering structures. However, the existing technology cannot effectively solve problems such as high concrete hydration heat and volume shrinkage, and there are still limitations in preventing cracks in large-volume lining concrete and large-scale engineering applications. Summary of the invention

[0006] The purpose of the present invention is to provide a low hydration heat micro-expansion composite fiber anti-cracking concrete and its preparation method and application, so as to solve the problem that ordinary concrete is prone to temperature cracks and shrinkage cracks due to the influence of the material's own characteristics and the engineering environment during the lining casting, maintenance and service of tunnels and underground projects.

[0007] To achieve the above-mentioned purpose, the present invention provides a low-hydration heat micro-expansion composite fiber anti-cracking concrete, wherein the components include, by mass, 275-316 parts of cement, 89-130 parts of fly ash, 40-125 parts of composite fibers, 0.1-0.5 parts of air entraining agent, 20-25 parts of expansion agent, 2-5 parts of water reducer, 750-850 parts of sand, 402-1005 parts of crushed stone and 150-200 parts of water.

[0008] Preferably, the composite fiber includes one or more of polypropylene fiber and steel fiber.

[0009] More preferably, the length of the steel fiber is about 35 mm and the length of the polypropylene fiber is about 6 mm.

[0010] Preferably, the crushed stone comprises one or more of continuously graded 5-20 mm crushed stone and continuously graded 20-40 mm crushed stone.

[0011] Preferably, the expansion agent is calcium sulphoaluminate expansion agent. The present invention adds the expansion agent to compensate for the drying shrinkage and temperature difference shrinkage of concrete, thereby inhibiting the occurrence of shrinkage cracks.

[0012] Preferably, the steel fibers are hook-end steel fibers.

[0013] Preferably, the sand is river sand with a particle size of 0-5 mm.

[0014] The method for preparing the above-mentioned low hydration heat micro-expansion composite fiber anti-cracking concrete comprises the following steps:

[0015] S1. Weigh 275-316 parts of cement, 89-130 parts of fly ash, 40-125 parts of composite fiber, 0.1-0.5 parts of air entraining agent, 20-25 parts of expansion agent, 2-5 parts of water reducer, 750-850 parts of sand, 402-1005 parts of crushed stone and 150-200 parts of water according to mass proportion;

[0016] S2, mixing cement, fly ash, sand and crushed stone, stirring evenly and drying to obtain a solid mixture;

[0017] S3, adding composite fiber to the solid mixture in S2, stirring evenly to obtain a solid base material for crack-proof concrete;

[0018] S4, mixing water, water reducing agent, air entraining agent and expansion agent, and stirring evenly to obtain an anti-cracking concrete mixture;

[0019] S5. Add the anti-cracking concrete solid base material in S3 to the anti-cracking concrete mixed liquid in S4 in batches, stirring while adding until the mixture is uniform, to obtain anti-cracking concrete.

[0020] Preferably, in S2, the cement is PO42.5 cement, and the ratio of the total amount of cement and fly ash to water is 1:0.4-0.5.

[0021] Preferably, in S4, the water reducing agent is a polycarboxylic acid water reducing agent. The present invention improves the fluidity and pumpability of concrete by adding an appropriate amount of water reducing agent to concrete, thereby ensuring its working performance.

[0022] The application of the above-mentioned low hydration heat micro-expansion composite fiber anti-cracking concrete is the application of the anti-cracking concrete in the lining pouring of tunnels and underground projects.

[0023] Preferably, when applied, the formwork can be removed 18 hours after the anti-cracking concrete lining is poured, and then cured every 6-7 hours for 7-14 days.

[0024] Therefore, the present invention adopts the above-mentioned low hydration heat micro-expansion composite fiber anti-cracking concrete and its preparation method and application, and its beneficial effects are:

[0025] 1. Steel fiber has the advantages of high strength and low cost, while polypropylene fiber has the characteristics of light weight, corrosion resistance, high toughness, etc. The advantages of the two can be fully combined through composite admixture. The low hydration heat micro-expansion composite fiber anti-cracking concrete provided by the present invention improves the internal structure of concrete by adding composite fibers, significantly improves the compressive and tensile strengths and anti-cracking ability of the anti-cracking concrete, and effectively reduces the cracking risk of tunnel and underground engineering lining concrete in complex environments;

[0026] 2. The present invention provides a low hydration heat micro-expansion composite fiber anti-cracking concrete, which can significantly reduce the heat of cement hydration reaction, prevent concrete temperature cracks, and help reduce the overall material cost of concrete by adding an appropriate amount of fly ash to partially replace cement;

[0027] 3. The present invention provides a low hydration heat micro-expansion composite fiber anti-cracking concrete, which can improve the volume stability of the anti-cracking concrete by adding an appropriate amount of expansion agent to the concrete, play a role in compensating for shrinkage, and prevent the occurrence of cracks caused by volume shrinkage of the concrete after solidification and hardening;

[0028] 4. The present invention provides a method for preparing a low hydration heat, micro-expansion composite fiber anti-cracking concrete, which has simple operating steps and convenient on-site processes. On the premise of ensuring that all components are fully mixed and uniform, it can significantly improve the efficiency of material preparation and on-site construction, so that the prepared anti-cracking concrete has good density, mechanical properties and anti-cracking ability, and has great engineering application value.

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a flow chart of a method for preparing a micro-expansion composite fiber anti-cracking concrete with low hydration heat according to the present invention;

[0031] Figure 2 It is a graph of mechanical properties data in Test Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0033] Example 1

[0034] A method for preparing low hydration heat micro-expansion composite fiber anti-cracking concrete comprises the following steps: Figure 1 shown.

[0035] S1. Weigh 275 parts of cement, 130 parts of fly ash, 39.5 parts of steel fiber, 0.9 parts of polypropylene fiber, 0.12 parts of air entraining agent, 20.3 parts of expansion agent, 4.4 parts of water reducer, 795 parts of sand, 402 parts of continuously graded 5-20 mm crushed stone, 603 parts of continuously graded 20-40 mm crushed stone and 180 parts of water by mass.

[0036] S2. Mix cement (PO42.5 cement), fly ash, sand and crushed stone (402 parts of continuously graded 5-20 mm crushed stone, 603 parts of continuously graded 20-40 mm crushed stone) in a water-cement ratio of 1:0.44 between the total amount of cement and fly ash and water. Stir well and then dry to obtain a solid mixture.

[0037] S3. Add composite fibers (39.5 parts of steel fibers and 0.9 parts of polypropylene fibers) to the solid mixture in S2, and stir evenly to obtain a solid base material for anti-cracking concrete.

[0038] S4. Mix water, water reducing agent, FK-AE type air entraining agent and expansion agent, and stir evenly to obtain an anti-cracking concrete mixture.

[0039] In S4, the water reducing agent is a polycarboxylic acid water reducing agent, and the expansion agent is a calcium sulfoaluminate expansion agent.

[0040] S5. Add the anti-cracking concrete solid base material in S3 into the anti-cracking concrete mixed liquid in S4 in 2-3 portions, stirring while adding until the mixture is uniform, to obtain anti-cracking concrete.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the amount of polypropylene fiber added is 2.7 parts, and the rest is the same as embodiment 1, and crack-resistant concrete is obtained.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that the amount of steel fiber added is 118.5 parts, and the rest is the same as embodiment 1, and crack-resistant concrete is obtained.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that the added amount of steel fiber is 118.5 parts and the added amount of polypropylene fiber is 2.7 parts, and the rest is the same as embodiment 1, and crack-resistant concrete is obtained.

[0047] Example 5

[0048] The difference between this embodiment and embodiment 1 is that the amount of cement added is 316 parts, the amount of fly ash added is 89 parts, and the rest is the same as embodiment 1, and crack-resistant concrete is obtained.

[0049] Example 6

[0050] The difference between this embodiment and embodiment 5 is that the amount of polypropylene fiber added is 2.7 parts, and the rest is the same as embodiment 5 to obtain anti-cracking concrete.

[0051] Example 7

[0052] The difference between this embodiment and embodiment 5 is that the amount of steel fiber added is 118.5 parts, and the rest is the same as embodiment 5, and crack-resistant concrete is obtained.

[0053] Example 8

[0054] The difference between this embodiment and embodiment 5 is that the added amount of steel fiber is 118.5 parts, the added amount of polypropylene fiber is 2.7 parts, and the rest is the same as embodiment 5, and crack-resistant concrete is obtained.

[0055] Application Example 1

[0056] When the anti-cracking concrete in Example 1 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is used for casting. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, it is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0057] Application Example 2

[0058] When the anti-cracking concrete in Example 2 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is cast. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the anti-cracking concrete is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0059] Application Example 3

[0060] When the anti-cracking concrete in Example 3 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is cast. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the anti-cracking concrete is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0061] Application Example 4

[0062] When the anti-cracking concrete in Example 4 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is used for casting. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, it is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0063] Application Example 5

[0064] When the anti-cracking concrete in Example 5 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is cast and the formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the anti-cracking concrete is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0065] Application Example 6

[0066] When the anti-cracking concrete in Example 6 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is cast. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the anti-cracking concrete is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0067] Application Example 7

[0068] When the anti-cracking concrete in Example 7 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is cast. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the anti-cracking concrete is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0069] Application Example 8

[0070] When the anti-cracking concrete in Example 8 is used in the lining casting of tunnels and underground projects, the anti-cracking concrete lining is used for casting. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, it is cured every 6-7 hours for 7-14 days to obtain an anti-cracking concrete sample.

[0071] Comparative Example 1

[0072] S1. Weigh 275 parts of cement, 130 parts of fly ash, 0.12 parts of air entraining agent, 4.4 parts of water reducer, 795 parts of sand, 402 parts of continuously graded 5-20 mm crushed stone, 603 parts of continuously graded 20-40 mm crushed stone and 180 parts of water by mass.

[0073] S2. Mix cement (PO42.5 cement), fly ash, sand and crushed stone (402 parts of continuously graded 5-20 mm crushed stone, 603 parts of continuously graded 20-40 mm crushed stone) in a water-cement ratio of cement and fly ash to water of 1:0.44. Stir well and dry to obtain a solid mixture.

[0074] S3. Mix water, polycarboxylic acid water reducing agent and FK-AE air entraining agent, and stir evenly to obtain a mixed liquid.

[0075] S4. Add the solid mixture in S2 into the mixed liquid in S3 in 2-3 times, stirring until the mixture is uniform, to obtain concrete.

[0076] When the above concrete is used in the lining pouring of tunnels and underground projects, anti-cracking concrete lining is used for pouring. The formwork can be removed 18 hours after the solidification and hardening is completed. Thereafter, the concrete is cured every 6-7 hours for 7-14 days to obtain a concrete sample.

[0077] Test Example 1

[0078] Compressive and tensile strength tests

[0079] The compressive strength and tensile strength tests were performed on the anti-cracking concrete samples in Examples 1-8 and the concrete samples in Comparative Example 1. The results are shown in Tables 1 and Figure 2 As shown, the tension-compression ratio is the ratio of tensile strength to compressive strength.

[0080] Table 1. Mechanical properties data of application examples 1-8 and comparative example 1

[0081]

[0082] Generally speaking, under the same strength conditions, the greater the tension-compression ratio, the better the toughness of the concrete material and the stronger the crack resistance. It can be seen from Table 1 that the mechanical properties and crack resistance of the anti-cracking concrete samples in Application Examples 1-8 are better than those of the concrete samples in Comparative Example 1. And by comparing Application Examples 1-4 and Application Examples 5-8, it can be seen that as the amount of composite fiber added increases, the compression ratio increases accordingly. Therefore, the anti-cracking concrete materials in Examples 1-8 are added with appropriate amounts of composite fibers and expansion agents, which respectively play the role of enhancing crack resistance and volume compensation.

[0083] Therefore, the present invention adopts the above-mentioned low hydration heat, micro-expansion composite fiber anti-cracking concrete and its preparation method and application, and reduces the heat of cement hydration reaction, resists concrete shrinkage and deformation, and improves the tensile and compressive strength of concrete by adding fly ash, composite fiber, expansion agent, water reducer, etc. into the concrete system, thereby achieving the purpose of significantly improving the anti-cracking performance of concrete, thereby effectively reducing the cracking risk of tunnel and underground engineering lining concrete under complex environments. At the same time, the preparation process has simple operating steps and convenient on-site processes. On the premise of ensuring that all components are fully mixed and uniform, the material preparation and on-site construction efficiency can be significantly improved, so that the prepared anti-cracking concrete has good density, mechanical properties and anti-cracking ability, and has great engineering application value.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A micro-expansion composite fiber anti-cracking concrete with low hydration heat, characterized in that: The components include, by mass, 275-316 parts of cement, 89-130 parts of fly ash, 40-125 parts of composite fiber, 0.1-0.5 parts of air entraining agent, 20-25 parts of expansion agent, 2-5 parts of water reducing agent, 750-850 parts of sand, 402-1005 parts of crushed stone and 150-200 parts of water.

2. The micro-expansion composite fiber anti-cracking concrete with low hydration heat according to claim 1, characterized in that: The composite fiber includes one or more of polypropylene fiber and steel fiber.

3. The micro-expansion composite fiber anti-cracking concrete with low hydration heat according to claim 1, characterized in that: The crushed stone includes one or more of continuously graded 5-20 mm crushed stone and continuously graded 20-40 mm crushed stone.

4. The micro-expansion composite fiber anti-cracking concrete with low hydration heat according to claim 1, characterized in that: The expansion agent is calcium sulphoaluminate expansion agent.

5. The micro-expansion composite fiber anti-cracking concrete with low hydration heat according to claim 2, characterized in that: The steel fiber is an end hook steel fiber.

6. A method for preparing the low hydration heat micro-expansion composite fiber anti-cracking concrete according to any one of claims 1 to 5, characterized in that: The following steps are included: S1. Weigh 275-316 parts of cement, 89-130 parts of fly ash, 40-125 parts of composite fiber, 0.1-0.5 parts of air entraining agent, 20-25 parts of expansion agent, 2-5 parts of water reducer, 750-850 parts of sand, 402-1005 parts of crushed stone and 150-200 parts of water according to mass proportion; S2, mixing cement, fly ash, sand and crushed stone, stirring evenly and drying to obtain a solid mixture; S3, adding composite fiber to the solid mixture in S2, stirring evenly to obtain a solid base material for crack-proof concrete; S4, mixing water, water reducing agent, air entraining agent and expansion agent, and stirring evenly to obtain an anti-cracking concrete mixture; S5. Add the anti-cracking concrete solid base material in S3 to the anti-cracking concrete mixed liquid in S4 in batches, stirring while adding until the mixture is uniform, to obtain anti-cracking concrete.

7. The method for preparing a low hydration heat micro-expansion composite fiber anti-cracking concrete according to claim 6, characterized in that: In S2, the cement is PO42.5 cement, and the ratio of the total amount of cement and fly ash to water is 1:0.4-0.

5.

8. The method for preparing a low hydration heat micro-expansion composite fiber anti-cracking concrete according to claim 6, characterized in that: In S4, the water reducing agent is a polycarboxylic acid water reducing agent.

9. An application of the low hydration heat micro-expansion composite fiber anti-cracking concrete according to any one of claims 1 to 5, characterized in that: Application of anti-crack concrete in lining pouring of tunnels and underground projects.

10. The use of a low hydration heat micro-expansion composite fiber anti-cracking concrete according to claim 9, characterized in that: When applied, the formwork can be removed 18 hours after the anti-cracking concrete lining is poured, and then cured every 6-7 hours for 7-14 days.